Physicochemical and techno-functional characterization of inulin extracted from chicory roots and Jerusalem artichoke tubers and exploring their ability to replace the fat in cakes - Rashid, Summer; Rakha, Allah; Butt, Masood Sadiq; Asghar, Muhammad (Progress in Nutrition, 2018)
Instant research was an attempt to elucidate the physicochemical characteristics of inulin extracted from chicory roots and Jerusalem artichoke tubers. The extracted inulin was assessed for various physicochemical analysis i.e. viscosity, water absorption index and water solubility index. Moreover, its techno-functional attributes involving water holding capacity, oil holding capacity, swelling capacity and solubility were also determined. Afterwards, extracted inulin from both the sources was used as a fat replacer in cakes. Purposely, eleven types of cakes were prepared by varying the concentration of chicory inulin (T1 to T5) and Jerusalem artichoke inulin (T6 to T10) @ 10%, 20%, 30%, 40% and 50% along with control (T0). The results of cake batter illustrated that viscosity decreased with increasing concentration of inulin and an inverse relationship was observed between water loss and increased inulin concentration. Results indicated that inulin supplemented designer foods have the potential to serve as fat replacer.